Assessing Self-Regulated Learning of Undergraduate EFL Students: Instrument Development and Validation - Rima, Rosmania; Juniardi, Yudi; Syafrizal, Syafrizal (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2025)
This study aimed to develop and validate an SRL questionnaire for undergraduate EFL students using Research and Development (R&D) approach with a simplified 3D model (define, design, and develop). The instrument assesses three key dimensions of SRL based on Zimmerman's theoretical framework: cognitive, motivational, and behavioral. Content validity was established through expert review, followed by a pilot study with 30 students. Pearson product-moment correlation confirmed item validity, all items exceeded r= 0.361 (p<0.05). Furthermore, the reliability analysis, using Cronbach's alpha, yielded a coefficient of 0.964, surpassing the acceptable threshold of 0.700. These findings collectively indicate that the developed SRL questionnaire possesses strong psychometric properties, making it valid and reliable instrument for measuring self-regulated learning among EFL students. This instrument enables educators to identify student strengths and weaknesses, informing targeted interventions and promoting autonomous learning practices among EFL students.